Walking in the Electrical Engineering History (Global Journal of Human-Social Science, 2013)
This project presents some new contributions to the science evolution concerning the Electrical Engineering. The collaborations of this project have the task to disclosure key realities that point out benefits to human society, through the applications of Electricity and its teaching. Electricity has been latent in nature and human beings have discovered and developed its potential through millenniums. Electricity utilization by ancient civilizations in the beginnings, its basic knowledge development and applications, as well as the interconnection among Electricity's shapes in nature are true examples of that and are covered in this project. Electrical Engineering fundamentals have been some keystones to state of art. The Electrical Engineering's fundamentals are base for the state-of-the-art and the Electrical Engineering well endowed teaching has cooperated for a building-up of high level professional people.
Keywords: electrical engineering; history; fundamentals; engineering education